2015
DOI: 10.1007/s00259-015-3231-2
|View full text |Cite
|
Sign up to set email alerts
|

Tau imaging in neurodegenerative diseases

Abstract: Aggregated tau protein is a major neuropathological substrate central to the pathophysiology of neurodegenerative diseases such as Alzheimer’s disease (AD), frontotemporal dementia, progressive supranuclear palsy, corticobasal degeneration and chronic traumatic encephalopathy. In AD, it has been shown that the density of hyperphosphorylated tau tangles correlates closely with neuronal dysfunction and cell death, unlike β-amyloid. Until now, diagnostic and pathologic information about tau deposition has only be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
97
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 77 publications
1
97
0
Order By: Relevance
“…In a recent debate on CSF, some researchers acknowledged the need for more systematic validation 88,89 ), while others regarded the currently available evidence as sufficient to support their use in the clinic 90 . If experts do not agree, it is not surprising that health care payers are reluctant to reimburse.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent debate on CSF, some researchers acknowledged the need for more systematic validation 88,89 ), while others regarded the currently available evidence as sufficient to support their use in the clinic 90 . If experts do not agree, it is not surprising that health care payers are reluctant to reimburse.…”
Section: Discussionmentioning
confidence: 99%
“…Several quinolone and benzimidazole derivatives have been created, the first of which was [ 18 F-THK523] which had several limitations, including high white matter retention and only 12-fold selectivity of tau over amyloid, preventing its clinical utility [36]. [38].…”
Section: Tau Imaging Approachesmentioning
confidence: 99%
“…However, it has some off-target binding (7) and exhibits a problematic kinetic profile, clearing slowly and failing to reach steady state in some brain regions (8)(9)(10)(11). On the other hand, some reports demonstrated that 18 F-AV1451 may also have some affinity for non-AD tauopathies (5). The aim of the present study was to develop a tau PET ligand with a pharmacokinetic profile superior to that of 18 F-AV1451 but with similar or better affinity to and selectivity for b-amyloid plaque.…”
mentioning
confidence: 99%
“…Because tau exists in six different isoforms, tau is subject to various posttranslational modifications, and tangles can have many ultrastructural conformations, the development of a specific tau PET tracer able to target tau pathology in AD remains daunting (4). Nonetheless, several tau-specific PET ligands have been developed in the past decade, and they were recently discussed in a review by Dani et al (5). Among the first of these identified was T807, a tracer developed by Siemens and then licensed to Eli Lilly, now known as 18 F-AV1451.…”
mentioning
confidence: 99%